2006
DOI: 10.2139/ssrn.932683
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rewards and Sanctions in Provision of Public Goods

Abstract: A growing number of field and experimental studies focus on the institutional arrangements by which individuals are able to solve collective action problems. Important in this research is the role of reciprocity and institutions that facilitate cooperation via opportunities for monitoring, sanctioning, and rewarding others. Sanctions represent a cost to both the participant imposing the sanction and the individual receiving the sanction. Rewards represent a zero sum transfer from participants giving to those r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
331
4
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 256 publications
(360 citation statements)
references
References 15 publications
20
331
4
5
Order By: Relevance
“…One reward point costs 1 money unit and the rewarded group member then gets, depending on the experiment, one or more money units as an additional payment. The results suggest that this mechanism can also stimulate contributions, in particular if the rewarded individual receives more than what it costs to reward (Sefton, Shupp, and Walker 2007;Rand et al 2009;Sutter, Haigner, and Kocher 2010). For example, in experiments comparable to Gächter et al (2008) summarized in Figure 4, Rand et al (2009) showed that achieved cooperation levels were as high as those under punishment.…”
Section: The Determinants Of Social Order Iii: Punishment and Other Imentioning
confidence: 92%
“…One reward point costs 1 money unit and the rewarded group member then gets, depending on the experiment, one or more money units as an additional payment. The results suggest that this mechanism can also stimulate contributions, in particular if the rewarded individual receives more than what it costs to reward (Sefton, Shupp, and Walker 2007;Rand et al 2009;Sutter, Haigner, and Kocher 2010). For example, in experiments comparable to Gächter et al (2008) summarized in Figure 4, Rand et al (2009) showed that achieved cooperation levels were as high as those under punishment.…”
Section: The Determinants Of Social Order Iii: Punishment and Other Imentioning
confidence: 92%
“…In this respect, it is interesting to note that many researchers implicitly assume such an equalcontributions norm when they analyze punishment behavior in public good games. For example, it is commonly assumed that punishment is motivated by deviations from either the average contribution Gächter, 2000, 2002;Anderson and Putterman, 2006;Sefton et al, 2007), the punisher's contribution (Gächter et al, 2008;Egas and Riedl, 2008;Sutter et al, 2008), or both (Masclet et al, 2003;Masclet and Villeval, 2008;Nikiforakis, 2008). In all these cases an equal-contributions norm is assumed.…”
Section: Focal and Conflicting Contribution Normsmentioning
confidence: 99%
“…Positive incentives become costly, but negative cheap, if success is fully achieved, i.e. all cooperate [10,[69][70][71].…”
Section: Box 4: the Carrot: The Role Of Rewards As Incentives For Coomentioning
confidence: 99%